EFFECT OF HYDRAZONES AGAINST INTRACELLULAR AMASTIGOTES OF Leishmania panamensis AND A PARASITIC CYSTEIN PROTEASE - MUÑOZ, Diana L.; CARDONA, Diana P.; CARDONA, Álvaro; CARRILLO, Lina M.; QUIÑONES, Winston; ECHEVERRI, Fernando; VÉLEZ, Iván D.; ROBLEDO, Sara M. (Vitae, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; @font-face font-family:Aldine401BT-RomanA; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:1 134676480 16 0 131072 0; @font-face font-family:Aldine401BT-ItalicA; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; @font-face font-family:"\@Aldine401BT-RomanA"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131072 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> In this paper, the synthesis of hydrazones derived from cromano, thiocroman, alkyl and aril hydrazones is described, as well as their leishmanicidal activity and their effect on cysteine proteases from L. (V) panamensis. A series of novel phenylthiochromane and benzyl and naphtyl derivatives are synthesized and evaluated for their cytotoxic and antileishmanial activities. Their effect on parasite cysteine protease is also evaluated. Only phenylthiochromane derivatives display some activity against Leishmania (V) panamensis but all compounds are inactive against parasitic cystein protease. These results may suggest a different mechanism of action for these compounds.